Development of Flipbook-Based Teaching Materials for Learning in Elementary School’s - Alpidsyah Putra; Fadhil Sidiq; Mahlianurrahman Mahlianurrahman (Jurnal Penelitian Pendidikan IPA, 2023)
Abstract: The use of digital teaching materials in the 21st century is considered very relevant to the development of information and communication technology in learning in elementary schools. Good teaching materials are teaching materials that include all the material needed in learning activities. This research aims to develop flipbook-based teaching materials in project activities to strengthen the profile of Pancasila students (P5) in elementary schools. The methodology used in this research uses the ADDIE model (analysis, design, development, implementation, and evaluation). Data analysis techniques use qualitative data analysis and quantitative data analysis. This research was conducted at SD Negeri 1 Langsa City, SD Negeri 11 Langsa City and SD Negeri 2 Seulalah. Based on the research results, the percentage of material expert validation was 88.95% with a very valid category; media expert validation obtained a percentage of 90.57% in the very valid category, while learning design experts obtained a percentage of 86.25% in the very valid category. From the research results above, it shows that this flipbook teaching material is very suitable to be applied as digitalization-based teaching material in the project to strengthen the profile of Pancasila students in elementary schools.